The primacy of politics social democracy and the making of Europe's twentieth century - Berman, Sheri (New York Cambridge University Press, 2006)
Political history in the industrial world has indeed ended, argues this pioneering study, but the winner has been social democracy - an ideology and political movement that has been as influential as it has been misunderstood. Berman looks at the history of social democracy from its origins in the late nineteenth century to today and shows how it beat out competitors such as classical liberalism, orthodox Marxism, and its cousins, Fascism and National Socialism by solving the central challenge of modern politics - reconciling the competing needs of capitalism and democracy. Bursting on to the scene in the interwar years, the social democratic model spread across Europe after the Second World War and formed the basis of the postwar settlement. This is a study of European social democracy that rewrites the intellectual and political history of the modern era while putting contemporary debates about globalization in their proper intellectual and historical context.
Includes bibliographical references and index.
Keywords: Socialism--Europe--History--20th century